The association between work‐related physical and psychosocial factors and musculoskeletal disorders in healthcare workers: Moderating role of fear of movement. Issue 1 (18th January 2022) - Keyaerts, Stijn; Godderis, Lode; Delvaux, Ellen; Daenen, Liesbeth
Abstract: Objectives: Knowledge is lacking on the interaction between fear of movement (FOM) and work‐related physical and psychosocial factors in the development and persistence of musculoskeletal disorders (MSDs). Methods: In this cross‐sectional study, 305 healthcare workers from several Belgian hospitals filled out a questionnaire including sociodemographic factors, work‐related factors (social support, autonomy at work, workload, and physical job demands), FOM, and MSDs for different body regions during the past year. Path analysis was performed to investigate (1) the association between the work‐related factors, FOM and MSDs, and (2) the moderating role of FOM on the association between the work‐related factors and MSDs among healthcare workers. Results: Complaints were most frequently located at the neck–shoulder region (79.5%) and lower back (72.4%). Physical job demands (odds ratio [OR] 2.38 and 95% confidence interval [CI] 1.52–3.74), autonomy at work (OR 1.64 CI [1.07–2.49]) and FOM (OR 1.07 CI [1.01–1.14] and OR 1.12 CI [1.06–1.19]) were positively associated with MSDs. Healthcare workers who experienced high social support at work (OR 0.61 CI [0.39–0.94]) were less likely to have MSDs. Fear of movement interacted negatively with workload (OR 0.92 CI [0.87–0.97]) and autonomy at work (OR 0.94 CI [0.88–1.00]) on MSDs. Conclusions: Work‐related physical and psychosocial factors as well as FOM are related to MSDs in healthcare workers. FOM is an important moderator of this relationship and should be assessed in healthcare workers in addition to work‐related physical and psychosocial factors to prevent or address MSDs.